2015
DOI: 10.1093/ajh/hpv002
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High Serum Soluble Corin and Hypertension: A Cross-Sectional Study in a General Population of China

Abstract: Our study showed that hypertensive participants had an increased serum corin level compared to those without hypertension. This finding suggests that corin may play a role in the pathology of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Our data, assessing a strictly connection between corin and systolic and diastolic blood pressure, were also confirmed by a cross-sectional study analyzing two-thousand patients, which revealed a relationship between high serum soluble corin and prevalent hypertension [13].…”
Section: Discussionsupporting
confidence: 82%
“…Our data, assessing a strictly connection between corin and systolic and diastolic blood pressure, were also confirmed by a cross-sectional study analyzing two-thousand patients, which revealed a relationship between high serum soluble corin and prevalent hypertension [13].…”
Section: Discussionsupporting
confidence: 82%
“…Blood cell analysis, including platelet count, plateletcrit, platelet distribution width, and mean platelet volume, was obtained using a BC-3200 hematology analyzer (Mindray Medical, Shenzhen, China). Fasting glucose, blood lipids including total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), and creatinine were measured by standard laboratory methods [30]. Diabetes was defined as fasting glucose over 7.0 mmol/L and/or receiving hypoglycemic medications in the last 2 weeks [31].…”
Section: Measurement Of Other Riskmentioning
confidence: 99%
“…In a population study involving 2498 adults of more than 30 years old, increased serum corin levels were associated with hypertension [75], obesity [76], dyslipidemia [77], and hyperglycemia [78]. High levels of plasma corin were found in patients with atrial fibrillation [79].…”
Section: Plasma Soluble Corin In Heart Disease and Strokementioning
confidence: 99%